Risks and Development Strategies of Cavendish Banana Agribusiness at PT Vinda Abadi Sejahtera, Bojonegoro Regency (International Journal of Scientific Research and Management (IJSRM), 2025)
This study analyzes the risk level of Cavendish banana agribusiness at PT Vinda Abadi Sejahtera, identifies the root causes of risks, and formulates agribusiness development strategies. The research was conducted descriptively with a purposive sampling approach at relevant locations. Data were collected through in-depth interviews and analyzed using the coefficient of variation to measure risk levels, the fishbone diagram for identifying root causes, and the SWOT matrix to formulate development strategies. The results show that PT Vinda Abadi Sejahtera faces low business risk, with a coefficient of variation below 10%, despite challenges in production, marketing, and management. The main risks include fruit damage due to inadequate storage, limited ripening facilities, and insufficient skills among partner farmers in handling harvested crops. The fishbone analysis identified risk factors related to human resources, methods, materials, environment, and technology. Meanwhile, the SWOT analysis placed the company in Quadrant I, enabling the implementation of strategies such as vertical integration, product diversification, and partnership optimization. The formulated development strategies are expected to help the company mitigate risks, enhance agribusiness sustainability, strengthen market competitiveness, and provide benefits to partner farmers in Bojonegoro Regency.